Aplicação de hidrogéis de quitosana/alginato com propriedade magnética na remoção de íons Pb (II) de sistemas aquosos - Facchi, Débora Pietrobon (2018)
Chitosan/alginate (CHT/ALG) and magnetic CHT/ALG/Fe3O4@SiO2 composites were successfully prepared and practiced as adsorbent materials to remove Pb(II) from aqueous systems. New hydrogel beads were yielded through an unpublished methodology, examining the ionic strength of the chitosan (CHT) solution. Polyvalent cations and toxic cross-linking agents such as glutaraldehyde and epichlorohydrin, repeatedly used as to concoct CHT/ALG based materials were not utilized in this study. The samples were characterized by scanning electron microscopy (MEV), energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), thermal analysis (TGA/DSC), Zeta potential measurements, among others. The addition of Fe3O4@SiO2 (7,9±3,4 nm) significantly modified the surface morphology of the composites. The CHT/ALG/ Fe3O4@SiO2(8) hydrogel comprising the highest Fe3O4@SiO2 content (8,0 wt.%), displayed magnetic feature and Zeta potential of -76,8 mV at pH 6,0. The kinetics and adsorption equilibrium studies chartered that Elovich and Redlich-Peterson mathematical models displayed the best fits for the experimental data, respectively. The magnetic composite CHT/ALG/Fe3O4@SiO2(8) pinpointed maximum adsorption capacity of the Pb(II) (qm) of 234,77 mg g-1 and adsorption/desorption cycles designed its reuse performance. The CHT/ALG/Fe3O4@SiO2(8) hydrogel was applied in battery effluent, garnering 99,04% Pb(II) removal, and diminishing the turbidity from 73 to 3,0 NTU. So, wastewater and battery effluents contaminated with Pb may be manipulated through an “eco-friendly” method, using a magnetic hybrid material based on CHT/ALG/Fe3O4@SiO2 as adsorbent.